Chitin scaffold combined with autologous small nerve repairs sciatic nerve defects - Bo Wang (Neural Regeneration Research, 2022)
Although autologous nerve transplantation is the gold standard for treating peripheral nerve defects, it has many clinical limitations. As an alternative, various tissue-engineered nerve grafts have been developed to substitute for autologous nerves. In this study, a novel nerve graft composed of chitin scaffolds and a small autologous nerve was used to repair sciatic nerve defects in rats. The novel nerve graft greatly facilitated regeneration of the sciatic nerve and myelin sheath, reduced atrophy of the target muscle, and effectively restored neurological function. When the epineurium of the small autogenous nerve was removed, the degree of nerve regeneration was similar to that which occurs after autogenous nerve transplantation. These findings suggest that our novel nerve graft might eventually be a new option for the construction of tissue-engineered nerve scaffolds. The study was approved by the Research Ethics Committee of Peking University People’s Hospital (approval No. 2019PHE27) on October 18, 2019.